METHODOLOGY OF MANAGEMENT OF DEVELOPMENT OF AGRIBUSINESS AND AGRICULTURAL FACTORIES - Sergey Gorlov; Janeta Popova (Вестник Северо-Кавказского федерального университета)
The article says about the necessity to study methodology of management of development of agrarian formations in the context of applying various scientific approaches. Provides a description and analysis of approaches to managing the development of agribusiness and agricultural factories. It is concluded that the use discussed in the article approaches to managing the development of agribusiness and agricultural factories is based on the methodological principle of the relationship between economic theory and real practice of management on the ground that not only confirms the objectivity of the original theoretical assumptions, but reflects their pragmatic nature.